2020
DOI: 10.1111/his.14080
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal tumours with RREB1–MRTFB fusion involving the mediastinum: extra‐glossal ectomesenchymal chondromyxoid tumours?

Abstract: Aims: Ectomesenchymal chondromyxoid tumour (ECT) is a rare benign intraoral tumour which almost exclusively presents as a small mass of the anterior dorsal tongue. Recently, the RREB1-MRTFB (previously known as MKL2) fusion gene has been identified in 90% of ECTs, all located in the tongue, emphasising its genetic distinctiveness. Here, we report two mesenchymal tumours involving the superior mediastinum of adult women with RREB1-MRTFB fusions. Methods and results: Both tumours presented as wellcircumscribed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Interestingly, Siegfried et al 10 showed in their case of biphenotypic “oropharyngeal” sarcoma that the RREB1‐MKL2 chimeric transcription factor encoded by this fusion gene produced an increase in MKL2 expression, thus mimicking the role of PAX3 in BSNS tumorigenesis. Just recently, a RREB1‐MKL2 fusion transcript was described in two cases of mesenchymal tumors involving the mediastinum 26 . These data suggest a potential role of RREB1 and MKL2 activation in oncogenesis leading to effects in the corresponding downstream pathways.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, Siegfried et al 10 showed in their case of biphenotypic “oropharyngeal” sarcoma that the RREB1‐MKL2 chimeric transcription factor encoded by this fusion gene produced an increase in MKL2 expression, thus mimicking the role of PAX3 in BSNS tumorigenesis. Just recently, a RREB1‐MKL2 fusion transcript was described in two cases of mesenchymal tumors involving the mediastinum 26 . These data suggest a potential role of RREB1 and MKL2 activation in oncogenesis leading to effects in the corresponding downstream pathways.…”
Section: Discussionmentioning
confidence: 83%
“…Just recently, a RREB1-MKL2 fusion transcript was described in two cases of mesenchymal tumors involving the mediastinum. 26 These data suggest a potential role of RREB1 and MKL2 activation in oncogenesis leading to effects in the corresponding downstream pathways.…”
Section: Discussionmentioning
confidence: 83%
“…To date, very few cases of extra‐glossal EMCMT have been reported 10–16 . However, only five genuine extra‐glossal EMCMTs have been verified by molecular testing (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Dickson et al detected a RREB1-MRTFB (formerly MKL2) fusion gene in 19/21 (90%) tumors by RNA-Seq and/or FISH as well as an EWSR1-CREM fusion product in a single tumor [2]. In addition to the ectomesenchymal chondromyxoid tumor, the RREB1-MRTFB fusion product has also been reported in a "biphenotypic oropharyngeal sarcoma" [14] as well as two mediastinal masses described as "extra-glossal ectomesenchymal tumors" [15]. The biphenotypic oropharyngeal sarcoma appears to be morphologically dissimilar to the current case; thus, the relationship of this report to ectomesenchymal chondromyxoid tumor remains uncertain.…”
Section: Discussionmentioning
confidence: 99%